A Group Intervention for HIV/STI Risk Reduction among Indian Couples - Ritu Nehra; Rashmi Bagga; Deborah Jones; Deepika; Sunil Sethi; Sunil Sharma; Stephen M. Weiss (Tabriz University of Medical Sciences, 2013)
Background: HIV in India is transmitted primarily by heterosexual contact. The present study sought to test the feasibility of a group HIV/STI risk reduction intervention among heterosexual couples in India. Methods: Focus groups and key informant interviews were used in 2008 to culturally tailor the intervention. Thirty sexually active and HIV/STI negative couples were enrolled and assessed regarding risk behavior and sexual barrier acceptability. Gender-concordant group sessions used cognitive behavioral strategies for HIV/STI prevention. Results: At baseline, male condom use was low (36%); no participants reported use of female condoms or vaginal gels. HIV knowledge was low; women had more HIV knowledge and more positive attitudes towards condom use than men. Post-intervention, willingness to use all barrier products (t = 10.0, P< .001) and intentions to avoid risk behavior increased (t = 5.62, P< .001). Conclusion: This study illustrates the feasibility of utilizing a group intervention to enhance HIV/STI risk reduction among Indian couples.